STUDY ON MONEY LAUNDERING PRACTICES FROM THE CRIMINAL ACTION RESULTS OF POLITICAL PARTIES - Denny Arinanda Kurnia (Universitas Islam Balitar, 2018)
General Election is a means of implementing the sovereignty of the people in direct, general, free, confidential, honest, and fair manner within the Unitary State of the Republic of Indonesia based on Pancasila and the Constitution of the Republic of Indonesia Year 1945. The election has many dynamics, expensive politics, lavish campaign funds for image politics, costly consulting and surveys of winning money, as well as money politics. The disclosure of political parties is highly important in the implementation of the elections due to the many streams of corruption used in the election. As a result, people do not believe in political parties, or some Indonesians are no longer sympathetic to political parties. The idea of a political party's financial transparency regulation should be carefully examined in the Indonesians’ election codification scheme. In the future, Indonesia must have a transparent and accountable campaign or political funding arrangement, along with strong sanctions and binding on the parties involved. Therefore, the people will restore their trust to the political parties, and assure the political parties to channel their aspirations in the granting of rights in the elections.